Bacterial community shifts in organically perturbed sediments - Andrew Bissett; Chris Burke; Perran L. M. Cook; John P. Bowman (Environmental Microbiology, 2007)
Summary Bacterial abundance, diversity and sediment function were investigated in organically perturbed sediments under Tasmanian salmon ( Salmo salar ) farms and adjacent reference sites. Bacterial numbers increased as farming and organic loading progressed through the farm stocking cycle and declined during the fallow period, although not to prestocking levels. Bacterial numbers ranged between approximately 2 × 10 8 and 3 × 10 9 cells per gram of sediment and were higher at cage sites than reference sites. Microelectrode and respiration data also demonstrated a clear effect of organic loading on sediments. Denaturing gradient gel electrophoresis (DGGE) showed that bacterial communities shifted both in response to farm loading and its cessation. A seasonal effect on microbial communities was also evident. Although bacterial communities did shift again during the fallowing period, this shift was not necessarily a return to preloading communities. The complexity of community shifts may be affected by the vast functional redundancy of bacterial groups. All bacterial communities, including those at reference sites, were highly dynamic. Respiration studies of amended sediments indicated that fish farm sediments were at least as resilient and diverse as reference site communities. The results of this study indicate that the functional redundancy of highly complex bacterial communities contributes to their robustness. The relationship between diversity and stability in bacterial communities remains unclear and requires further investigation before an understanding of bacterial response to perturbation is possible.